IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT RUMAH TANGGA MISKIN DESA MONTOR KECAMATAN BANYUATES KABUPATEN SAMPANG - Cahyono, Anjar (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
The purpose of this study to determine Raskin Program Implementation in the village of the District Montor Banyuates Sampang, seen from the implementation process, namely How Poor Rice Program and Factors of success and failure in the implementation of Raskin. Data analysis technique used is Data Reduction Based on the results of this research is that the implementation of Raskin in the village of the District Montor Banyuates not run according to the rules It can be known First, regarding any number of rice distributed, second often incompatible with what was programmed by government, the price of which is not in accordance with the initial planning, the quality of rice ugly Fourth, fifth discrepancies raskin prices in 2015, the Sixth of a delay in the disbursement of Raskin of area is not deposited to Bulog. Factors of success and failure seen from the communication that exists is not good because it was done quickly and the lack of time for the executive to conduct socialization program, Executive manager of Raskin in the village Montor poorly for full implementation Rice Miskin, implementor at village Montor less prudent in implementing the program Raskin so that the distribution of rice Poor (Raskin) is not effective and not well targeted, and Society in the receiving Raskin mostly unaware of the institution / organization what poor rice was issued, in the implementation of Raskin Community, the main target of the program, it is expected that in every implementation kegiatanya rice for the poor program (Raskin) in the village of the District Montor there Banyuates control or supervision by local authorities to prevent irregularities in the distribution of rice. Keyword : mplementation, Program Beras Miskin, Public Welfare, Sampang